Howard and Christine Watkins Visit England-Greenwich - Watkins, Howard::::::::: (1988)
Ann Finer and Christine Watkins by statue of General James Wolfe in Greenwich Park Commemorated General's defeat of the French in Quebec, securing Canada for the British